2023
DOI: 10.3390/polym15020426
|View full text |Cite
|
Sign up to set email alerts
|

Waste Paper as a Valuable Resource: An Overview of Recent Trends in the Polymeric Composites Field

Abstract: This review focuses on polymeric waste-paper composites, including state-of-the-art analysis with quantitative and qualitative discussions. Waste paper is a valuable cellulose-rich material, produced mainly from office paper, newspaper, and paper sludge, which can be recycled and returned to paper production or used in a new life cycle. A systematic literature review found 75 publications on this material over the last 27 years, with half of those published during the last five years. These data represent an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 103 publications
3
12
0
Order By: Relevance
“…Importantly, the weight of the finished composites increased slightly when compared to the composites without the addition of paper waste. This outcome is in accordance with previous studies that indicated that paper waste provides a good filler material for improving the properties of composite materials, particularly when the density attributes need to be improved [ 22 , 23 , 27 , 47 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, the weight of the finished composites increased slightly when compared to the composites without the addition of paper waste. This outcome is in accordance with previous studies that indicated that paper waste provides a good filler material for improving the properties of composite materials, particularly when the density attributes need to be improved [ 22 , 23 , 27 , 47 ].…”
Section: Resultssupporting
confidence: 92%
“…Several previous studies have utilized paper waste to improve the qualities of various composite materials because cellulose fibers are known for their high strength and stiffness. When these cellulose fibers are mixed into composite materials, they can reinforce the matrix material [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Waste paper has a high cellulose content. 25 Paper constitutes the second largest component of global municipal solid waste. Recycling paper reduces energy consumption for the production of new materials.…”
Section: Introductionmentioning
confidence: 99%
“…The use of paper has shown an explosive growth trend in the past decades, which has not only caused the decrease of trees but also caused great damage to the atmospheric environment. , Cellulose, as the main component in paper, has the characteristics of renewability and biodegradability and is an environmentally friendly material with a wide range of uses. , Nowadays, cellulose has become an important part of many high-tech fields (such as the chemical industry, materials, medical treatment, etc. ). At the same time, cellulose is also one of the common polysaccharides that are often used to discuss its internal structure and bonding in the teaching of polymer chemistry .…”
Section: Introductionmentioning
confidence: 99%